Molecular and cytogenetic characterization of expanded B-cell clones from multiclonal versus monoclonal B-cell chronic lymphoproliferative disorders. - Henriques, A (2014)
Chronic antigen-stimulation has been recurrently involved in the earlier stages of monoclonal B-cell lymphocytosis, chronic lymphocytic leukemia and other B-cell chronic lymphoproliferative disorders. Among these individuals, expansion of ≥2 B-cell clones has been frequently reported; potentially, such coexisting clones have a greater probability of interaction with common immunological determinants. Here, we comparatively analyzed the B-cell receptor repertoire and the molecular profile, as well as the phenotypic, cytogenetic and hematological features of 228 chronic lymphocytic leukemia-like and non-chronic lymphocytic leukemia-like clones between multiclonal (n=85 clones from 41 cases) versus monoclonal (n=143 clones) monoclonal B-cell lymphocytosis, chronic lymphocytic leukemia and other B-cell chronic lymphoproliferative disorders. The B-cell receptor of B-cell clones from multiclonal cases showed a slightly higher degree of HCDR3 homology than B-cell clones from monoclonal cases, in association with unique hematological (e.g. lower B-lymphocyte counts) and cytogenetic (e.g. lower frequency of cytogenetically altered clones) features usually related to earlier stages of the disease. Moreover, a subgroup of coexisting B-cell clones from individual multiclonal cases which were found to be phylogenetically related, showed unique molecular and cytogenetic features: they more frequently shared IGHV3 gene usage, shorter HCDR3 sequences with a greater proportion of IGHV mutations and del(13q14.3), than other unrelated B-cell clones. These results would support the antigen-driven nature of such multiclonal B-cell expansions, with potential involvement of multiple antigens/epitopes.